2023
DOI: 10.1111/codi.16575
|View full text |Cite
|
Sign up to set email alerts
|

Study of capsule endoscopy delivery at scale through enhanced artificial intelligence‐enabled analysis (the CESCAIL study)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In 2022, the research conducted by Piccirelli et al investigating the diagnostic accuracy of Express View of IntroMedic achieved a 97% sensitivity and 100% specificity [75] . As AI polyp detection tools are commercially available for colonoscopy, such as FujiFilm's CADeye [76] and EndoBRAIN (Olympus), the imminent release and usage of AI tools for capsule endoscopy is expected with these promising results, which will likely only be further supported by future research such as the planned multi-centre CESCAIL study [77] [Table 4]. Li and Meng [24] Erosions and ulcers…”
Section: Polyps and Tumoursmentioning
confidence: 99%
“…In 2022, the research conducted by Piccirelli et al investigating the diagnostic accuracy of Express View of IntroMedic achieved a 97% sensitivity and 100% specificity [75] . As AI polyp detection tools are commercially available for colonoscopy, such as FujiFilm's CADeye [76] and EndoBRAIN (Olympus), the imminent release and usage of AI tools for capsule endoscopy is expected with these promising results, which will likely only be further supported by future research such as the planned multi-centre CESCAIL study [77] [Table 4]. Li and Meng [24] Erosions and ulcers…”
Section: Polyps and Tumoursmentioning
confidence: 99%
“…CCE is also currently being evaluated for polyp detection utilizing Artificial intelligence to enhance pathways for utility ( Table 2 ) 55 , 56 :…”
Section: Use Of Cce In Clinical Practicementioning
confidence: 99%
“…The stages of integrating artificial intelligence (AI) into the CCE process detailed by Robertson et al propose a scenario where AI could initially replace the pre-reading process and eventually take on the responsibility for analysing the entire CCE video prior to the clinician’s validation and reporting. 12 14 This proposal comprises of different stages. It suggested that the clinician would be presented with all the polyps’ images without a comprehensive review of the whole CCE video.…”
Section: Introductionmentioning
confidence: 99%